Do Fundamentals Matter? Evidence of IPO Underpricing in Indonesia's Consumer Goods Sector - Ana Fitrotun Nisa; Henni Indriyani (Journal Of Economic Cluster, 2025)
The phenomenon of stock underpricing is an anomaly frequently observed during Initial Public Offering (IPO), coinciding with the rapid development of the capital market. This study aims to analyze the influence of Auditor Reputation, Return On Assets (ROA), Financial Leverage, and Earning Per Share (EPS) on the degree of stock underpricing. This quantitative study utilizes secondary data from companies in the primary consumer goods sector that conducted an IPO on the Indonesia Stock Exchange (IDX) during the 2018–2022 period. Using a purposive sampling technique, a sample of 33 companies was obtained. Data analysis was performed using a multiple linear regression model, where underpricing was measured by the initial return. The empirical results indicate that the variables Auditor Reputation, Return On Assets (ROA), Financial Leverage, and Earning Per Share (EPS) do not have a significant partial effect on stock underpricing. These findings suggest that other non-financial and non-accounting factors may be more dominant in determining the IPO initial return in this sector on the IDX. Practically, this implies that investors should not rely on fundamental metrics (ROA/EPS) as primary indicators for purchasing IPO stocks in this sector, as they are proven to have no significant impact.